(untitled) (Scientific journal of the Fergana State University, 2026)
The article examines the emergence of the first socio-political views in Ancient China, exploring the development of moral norms in society and their elevation to the level of laws. It also reveals a characteristic feature of ancient political doctrines: in practically all countries, politics was always considered within the framework of moral principles and in inseparable unity with them.